2014
DOI: 10.1016/j.ijscr.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of ‘drop foot’ in the pediatric age group: Proximal fibular osteochondroma a report of 5 cases

Abstract: INTRODUCTIONThe fibular nerve is the most frequent site of neural entrapment in the lower extremity and the third most common site in the body, following the median and ulnar nerves. The peroneal nerve is commonly injured upon trauma. Additionally, a dropped foot might be a symptom related to the central nervous system or spinal pathologies in pediatric patients. Entrapment of the peripheral nerve as an etiologic cause should be kept in mind and further analyzed in orthopedic surgery clinics.PRESENTATION OF CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Compression of the CPN frequently occurs in association with lesions at the neck of the fibula in 54% of all cases; its traumatic etiology represents 40% whereas its tumoral origin stands for only 6% [ 8 ]. Spur or tumoral structure formation at the level of the proximal fibula can potentially apply pressure to the surrounding structures especially on the CPN [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compression of the CPN frequently occurs in association with lesions at the neck of the fibula in 54% of all cases; its traumatic etiology represents 40% whereas its tumoral origin stands for only 6% [ 8 ]. Spur or tumoral structure formation at the level of the proximal fibula can potentially apply pressure to the surrounding structures especially on the CPN [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Kline [ 12 ] reported 302 cases of peroneal nerve injuries and described only one patient who presented bilateral peroneal compression by exostosis of the head of the fibula. Only a few cases of entrapment of the peroneal nerve by cartilaginous exostosis have been reported so far [ 9 ]. It is assumed that paralysis in our case is secondary to exostosis and provoked by the trauma to the knee.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33] After retrieval from the literature, we observed that the symptomatology was mostly related with peroneal nerve compression except the popliteal artery-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiographs (anteroposterior and lateral view) of the leg with knee revealed a large cauliflower-like growth arising from proximal fibula ( Figure 4 [13][14][15][16][17][18][19] 15 articles (except surgical technique reports) [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] 14 articles in literature [20][21][22][23][24][25][26][27][28][29][30][31][32][33] 14 articles in literature [20][21][22][23][24][25][26][27][28][29][30][31][32]…”
Section: Case Reportsmentioning
confidence: 99%
“…Geçirilmiş olan travmalar sonucunda ortaya çıkan artritik değişikler, deformiteler ve anormal kallus varlığı, direkt grafiler ile değerlendirilebilir. [8,19] Fibula başı çevresindeki yapısal değişiklikler veya eksositoz gibi tümöral gelişimler de ilk olarak direkt grafi ile değerlendirilir. Manyetik rezonans (MR) görüntüleme, fibula başı çevresindeki kistik oluşumları ve solid kitlelerin ayırıcı tanısı açısından yardımcı olabilir.…”
Section: Tani Testleri̇unclassified